Ethnobotanical approach of plant diversity and market availability used for diabetes management in Benin and Burkina Faso, West Africa - Compaoré, Souleymane; Legba, Ingrid S.; Kaboré, Boukaré; Belemnaba, Lazare; Ouédraogo, Sylvin; Thiombiano, Adjima; Adomou, Aristide C. (Ethnobotany Research and Applications, 2026)
Background: The management of diabetes in sub-Saharan African countries remains a major challenge for low-income populations. This study provides a comparative analysis of the plants used by herbalists to manage diabetes in Benin and Burkina Faso. Methods: Market surveys were conducted among 27 herbalists in each country from 2023 to 2024. A semi-structured interview was performed with herbalists who agreed to participate. The main information collected included the local names of the plants sold, the methods of preparation and administration of the recipes, and the recipe prices. Diversity, similarity, market availability indices, and informant consensus factors were determined. The most cited plants underwent phytochemical screening and analysis of chemical compounds. Results: forty species were identified in each country, but with a very low similarity index (Ij = 0.0256). Shannon, Simpson, and Pielou index revealed comparable diversity structures between the two countries, despite a vastly different floristic composition. The market availability index was not correlated (p = 0.35; p = 0.85) with conservation status (IUCN), suggesting that the presence of species on the markets does not depend on their overall threat level. However, bark is mainly cited (38.5 %) in Burkina Faso, while leaves are dominant (38.3 %) in Benin. The most cited species reveals the presence of chemical compounds of interest for diabetes management. Conclusions: these results highlight the importance of local knowledge in diabetes management in both countries, while raising sustainability concerns about the exploitation of plant resources. Keywords: market survey, diabetes, species diversity, management, West Africa